Midostaurin treatment in FLT3-mutated acute myeloid leukemia and systemic mastocytosis - Kayser, Sabine; Levis, Mark J.; Schlenk, Richard Friedrich (Expert review of clinical pharmacology, 2017)
Introduction: A number of tyrosine kinase inhibitors (TKIs) have been developed that inhibit the constitutively activated kinase activity caused by activating tyrosine kinase mutations, such as FLT3 or KIT, thus interrupting signaling pathways. Currently, midostaurin is the only approved TKI as monotherapy for aggressive systemic mastocytosis (SM), SM with associated hematological neoplasm, or mast cell leukemia displaying a KIT mutation as well as in combination with standard intensive chemotherapy for adult patients with newly diagnosed FLT3-mutated acute myeloid leukemia (AML).Areas covered: We provide a concise review of the pharmacology, tolerability and clinical efficacy of midostaurin and emerging new treatment options for ASM and FLT3-mutated AML.Expert commentary: Currently, midostaurin is the only approved TKI in aggressive SM, SM with associated hematological neoplasm, or mast cell leukemia inducing responses including complete remissions. With regard to AML, midostaurin is the first drug to receive regulatory approval in this indication in the molecularly defined subgroup of AML with FLT3 mutations. By introduction of this new standard in AML with FLT3 mutations, the bare has been raised for future approvals of next generation FLT3 inhibitors which will be based increasingly on head to head comparisons with midostaurin.
Gesehen am 30.07.2018